46.4k views
0 votes
Use the quadratic formula to solve the equation. 2x2−6x+1=0 Enter your answers, in simplified radical form, in the boxes.

2 Answers

0 votes
X= -b +- square root of b^2-4ac
——————-
2a

6 +- square root of 36-4(2)(1)
———
4

6+- square root of 32
———
4

6+- 4 square root of 2
———
4

3 +- 2 square root of 2
———
2
User Qiubit
by
5.7k points
3 votes

Answer with Step-by-step explanation:

We have to solve the equation 2x²-6x+1=0

the solution of the equation ax²+bx+c=0 is given by


x=(-b+√(b^2-4ac))/(2a)\ and\ x=(-b-√(b^2-4ac))/(2a)

Here a=2,b=-6 and c=1


x=(6+√(6^2-4* 2* 1))/(2)\ and\ x=(6-√(6^2-4* 2* 1))/(2)\\\\x=(6+√(36-8))/(2)\ and\ x=(6-√(36-8))/(2)\\\\x=(6+√(28))/(2)\ and\ x=(6-√(28))/(2)\\\\x=(6+2√(7))/(2)\ and\ x=(6-2√(7))/(2)\\\\x=3+√(7)\ and\ x=3-√(7)

Hence, solution of 2x²-6x+1=0 is:


x=3+√(7)\ and\ x=3-√(7)

User Gizmo
by
5.4k points